2016
DOI: 10.1002/ana.24609
|View full text |Cite
|
Sign up to set email alerts
|

Transcranial Doppler versus transthoracic echocardiography for the detection of patent foramen ovale in patients with cryptogenic cerebral ischemia: A systematic review and diagnostic test accuracy meta‐analysis

Abstract: TCD is more sensitive but less specific compared to TTE for the detection of PFO in patients with cryptogenic cerebral ischemia. The overall diagnostic yield of TCD appears to outweigh that of TTE.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
90
2
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(98 citation statements)
references
References 71 publications
1
90
2
5
Order By: Relevance
“…When comparing TCD with contrast-enhanced TTE for detection of PFO, a recent meta-analysis suggested it to be more sensitive but less specific. 41 When compared with TEE, however, there remains controversy regarding which modality is most sensitive. 35, 42 The uncertainty is likely related to differences in what is used as the gold standard for the presence of a PFO.…”
Section: Cryptogenic Stroke and Pfomentioning
confidence: 99%
“…When comparing TCD with contrast-enhanced TTE for detection of PFO, a recent meta-analysis suggested it to be more sensitive but less specific. 41 When compared with TEE, however, there remains controversy regarding which modality is most sensitive. 35, 42 The uncertainty is likely related to differences in what is used as the gold standard for the presence of a PFO.…”
Section: Cryptogenic Stroke and Pfomentioning
confidence: 99%
“…It can also aid in evaluating cryptogenic stroke by detecting a patent foramen ovale (PFO) or in identifying emboli in the setting of symptomatic spontaneous dissections. 5,8,20 Whereas these modalities are used primarily to determine the cause of an acute ischemic stroke, 4D CTA and MRA can be more helpful in identifying the true infarct core and potential The evaluation and management of acute ischemic stroke has primarily relied on the use of conventional CT and MRI techniques as well as lumen imaging sequences such as CT angiography (CTA) and MR angiography (MRA). Several newer or less-established imaging modalities, including vessel wall MRI, transcranial Doppler ultrasonography, and 4D CTA and MRA, are being developed to complement conventional CT and MRI techniques.…”
mentioning
confidence: 99%
“…4 High sensitivity has been reported for TCD (89%-97%) and some authors found TCD to be even more sensitive than TEE to detect RLC, and false-negative TCDs have been demonstrated to be due to small-size PFO. [12][13][14][15][16][17][18][19] In the present study, we evaluated the use of TCD to detect RLC and we compared the results with those obtained by TTE and TEE.…”
mentioning
confidence: 99%